Interatomic electronic decay driven by nuclear motion - Sisourat, Nicolas; Sann, Hendrik; Kryzhevoi, Nikolai V.; Kolorenč, Přemysl; Havermeier, Tilo; Sturm, Felix; Jahnke, Till; Kim, Hong-Keun; Dörner, Reinhard; Cederbaum, Lorenz S. (Physical review letters, 2010)
The interatomic electronic decay after inner-valence ionization of a neon atom by a single photon in a neon-helium dimer is investigated. The excited neon atom relaxes via interatomic Coulombic decay and the excess energy is transferred to the helium atom and ionizes it. We show that the decay process is only possible if the dimer’s bond stretches up to 6.2 Å, i.e., to more than twice the equilibrium interatomic distance of the neutral dimer. Thus, it is demonstrated that the electronic decay, taking place at such long distances, is driven by the nuclear motion.
Gesehen am 09.08.2023